Perceived Effects Of Withholding Teachers’ Annual Salary Increment On Their Job Morale In Public Secondary Schools In Arusha Region, Tanzania - Ephrahem, Goodluck; Ogoti Okendo, Evans; Salema, Dr. Victorini (International Journal of Scientific Research and Management (IJSRM), 2023)
This study examined the perceived effects of withholding teachers’ annual salary increment on their job morale in public secondary schools in Arusha region, Tanzania. This study was guided by Expectancy Theory by Vroom (1964). The study adopted convergent research design under mixed methods approach. The target population was 5057 with sample size 513 respondents. Random and non-random sampling techniques were used to sample teachers, HOSs, WEOs, SAMs TSCs officers, DEOs, DEDs. Content and face validity for quantitative data collection instruments were ensured by three research experts in MWECAU. Reliability of the questionnaire were tested by using Cronbach’s Alpha Technique with coefficient of 0.88, 0.85, and 0.9 were obtained for teachers, HOSs, and WEOs questionnaires respectively and reliability of qualitative data was done by triangulation.  Descriptive and inferential statistics were used to analyze quantitative data. Pearson correlation was used to test hypothesis. Thematic analysis was used to analyze qualitative data and direct quotations were used to present data. The study found that withholding teachers’ annual salary increment had several effects including lowered teachers’ job morale in teaching. The study concluded that, there was a significant relationship of 0.557 between the mean scores of perceived effects of withholding teachers’ annual salary increment and teachers’ job morale in teaching. The study recommends the local government authority should facilitate in resuming teachers’ annual salary increment by convincing the central government. The MoEST should resume teachers’ annual salary increment so as to revive teachers’ job morale in teaching in public secondary schools in Arusha region.